2020
DOI: 10.1093/qjmed/hcaa164
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas (XEN) inhalation ameliorates airway inflammation in asthma and COPD patients

Abstract: Summary Background Hydrogen was proven to have anti-oxidative and anti-inflammation effects to various diseases. Aim We wish to investigate the acute effects of inhaled hydrogen on airway inflammation in patients with asthma and chronic obstructive pulmonary disease (COPD). Design Prospective study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
3
44
1
Order By: Relevance
“…Wang et al found that the levels of monocyte chemoattractant protein-1 (MCP-1), IL-4, and IL-6 in peripheral blood decreased significantly after inhalation of 2.4% hydrogen gas via a nasal catheter for 45 min in the patients with chronic obstructive pulmonary disease. Hydrogen reduces airway inflammation by reducing cytokine levels (65). According to the above studies, the use of hydrogen gas can reduce the destructive cytokine storm and lung injury caused by SARS-CoV-2 in the early stage of the COVID-19, stimulate sputum drainage, and ultimately reduce the incidence of severe disease (49).…”
Section: Cytokinesmentioning
confidence: 99%
“…Wang et al found that the levels of monocyte chemoattractant protein-1 (MCP-1), IL-4, and IL-6 in peripheral blood decreased significantly after inhalation of 2.4% hydrogen gas via a nasal catheter for 45 min in the patients with chronic obstructive pulmonary disease. Hydrogen reduces airway inflammation by reducing cytokine levels (65). According to the above studies, the use of hydrogen gas can reduce the destructive cytokine storm and lung injury caused by SARS-CoV-2 in the early stage of the COVID-19, stimulate sputum drainage, and ultimately reduce the incidence of severe disease (49).…”
Section: Cytokinesmentioning
confidence: 99%
“…Accordingly, hydrogen treatment can reduce the levels of TNF-α, IL-1, IL-1 β, IL-6, IL-8, HMGB1, CCL2, and Egr-1 in lung tissue in an animal model ( Huang et al, 2010a ). Furthermore, inhaling hydrogen for 45 minutes can reduce airway inflammation in patients with asthma and COPD ( Wang et al, 2020 ). At the same time, previous studies have shown that an increase in IL-10 can inhibit the synthesis and release of inflammatory cells and colony stimulating factors ( Laveda et al, 2006 ).…”
Section: Hydrogen and The Cytokine Stormmentioning
confidence: 99%
“…For the case of the benefits observed in damaged lung, a study performed in mice with chronic lung injury induced by hypoxia/re-oxygenation, demonstrated that inhalation of molecular hydrogen attenuated preexistent lung injuries ( 101 ). When 20 patients with asthma or Chronic Obstructive Pulmonary Disease inhaled a 2.4% hydrogen-containing steam mixed gas (for 45 min), attenuation of their inflammatory airway status (decrease of selected pro-inflammatory biomarkers) was observed ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with molecular antioxidants reduces intracellular levels of influenza virus polymerase, providing a possible mechanism of viral titer reduction in response to antioxidant treatment (98). Additionally, it has been demonstrated that small antioxidant molecules, specifically molecular hydrogen, produce anti-inflammatory effects over multiple COVID-19 target organs, such as the lung, kidney, liver and brain, when compromised by acute and/or chronic diseases (97,(99)(100)(101)(102). For instance, a study suggested that intraperitoneal administration of hydrogen-rich saline to rats with ischemia/reperfusion-induced acute kidney injury, prevented fibrosis damage and improved renal function (99).…”
Section: Baseline Severity Progressionmentioning
confidence: 99%